Molecular and cell-based therapies for muscle degenerations: a road under construction - Berardi, Emanuele; Annibali, Daniela; Cassano, Marco; Crippa, Stefania; Sampaolesi, Maurilio (Frontiers in Physiology, 2014)
Despite the advances achieved in understanding the molecular biology of muscle cells in the past decades, there is still need for effective treatments of muscular degeneration caused by muscular dystrophies and for counteracting the muscle wasting caused by cachexia or sarcopenia. The corticosteroid medications currently in use for dystrophic patients merely help to control the inflammatory state and only slightly delay the progression of the disease. Unfortunately, walkers and wheel chairs are the only options for such patients to maintain independence and walking capabilities until the respiratory muscles become weak and the mechanical ventilation is needed. On the other hand, myostatin inhibition, IL-6 antagonism and synthetic ghrelin administration are examples of promising treatments in cachexia animal models. In both dystrophies and cachectic syndrome the muscular degeneration is extremely relevant and the translational therapeutic attempts to find a possible cure are well defined. In particular, molecular-based therapies are common options to be explored in order to exploit beneficial treatments for cachexia, while gene/cell therapies are mostly used in the attempt to induce a substantial improvement of the dystrophic muscular phenotype. This review focuses on the description of the use of molecular administrations and gene/stem cell therapy to treat muscular degenerations. It reviews previous trials using cell delivery protocols in mice and patients starting with the use of donor myoblasts, outlining the likely causes for their poor results and briefly focusing on satellite cell studies that raise new hope. Then it proceeds to describe recently identified stem/progenitor cells, including pluripotent stem cells and in relationship to their ability to home within a dystrophic muscle and to differentiate into skeletal muscle cells. Different known features of various stem cells are compared in this perspective, and the few available examples of their use in animal models of muscular degeneration are reported. Since non coding RNAs, including microRNAs (miRNAs), are emerging as prominent players in the regulation of stem cell fates we also provides an outline of the role of microRNAs in the control of myogenic commitment. Finally, based on our current knowledge and the rapid advance in stem cell biology, a prediction of clinical translation for cell therapy protocols combined with molecular treatments is discussed.